The dark side - Steel, Danielle (New York, New York : Random House Large Print, 2019)
"Zoe Morgan's childhood was marked by her younger sister's tragic illness, watching as her parents dedicated themselves completely to her final days and then divorced. As a young woman driven by these painful memories, Zoe sets the bar high for herself, studying hard and pursuing a career in the nonprofit world, where her deep compassion for disadvantaged children finds a focus. When Zoe falls in love and has her own child, she is determined to be a perfect mother as well. But before long, old scars long dormant begin to pull Zoe to the edge of an abyss too terrifying to contemplate. As Zoe is haunted by the ghosts of the past, her story will become a race against time and a tale of psychological suspense that no reader will soon forget"--
"Published ... in association with Delacorte Press, an imprint of Random House, a division of Penguin Random House LLC, New York"--Copyright page.
A novel.
Keywords: Families -- Fiction; Motherhood -- Fiction; Long term illnesses -- Children -- Fiction; Divorce -- Parents -- Fiction; Parent-child relationships -- Fiction; Large type books; Domestic fiction; Psychological fiction; Thrillers (Fiction)